You are on page 1of 8

GITIMH3 94107 Sequences & Series Page 1

Sequences
15/10/98
 A sequence is a set of numbers, which forms a mathematical pattern.
 It is denoted by ‘Tn’, where ‘n’ is a positive integer.

E.g. The nth term of a sequence is given by Tn = 103 – 3.n


(a) Find the first 3 terms
(b) Find the value of ‘n’ for the first negative term in the sequence

A (a) T1 = 103 – 3  1 = 100


T2 = 103 – 3  2 = 97
T3 = 103 – 3  3 = 94
(b) Tn < 0
103 – 3n < 0
n > 34 1/3
 n > 35

Sigma Notation ():


5
E.g. (1)  3.n
n 1
5
 3.n = (3  1) + (3  2) + (3  3) + (3  4) + (3  5)
n 1
= 45

7
E.g. (2) n  5
n 4
7
 n  5 = (4 – 5) + (5 – 5) + (6 – 5) + (7 – 5)
n 4
=2

Luke Cole Page 1


GITIMH3 94107 Sequences & Series Page 2

Arithmetic Sequence or Arithmetic Progression


(AP)
20/10/98
 A sequence in which each term after the first is formed by adding a constant
number, this constant number is referred to as the common difference ‘d’.

E.g. 8, 10, 12, 14,… Common difference  d = 2 Since, (10 – 8) = (12 – 10)
15, 12, 9, 6,… Common difference  d = – 3 Since, (12 – 15) = (9 – 12)

The nth Term of an AP:


Equation: Tn = a + (n – 1)d
Tn = nth term
a = First term
n = Number of terms
d = Common difference

Proof:
So, T1 = a
T2 = a + d
T3 = a + 2d
 Tn = a + (n – 1)d

E.g. Find the 20th term of 5, 8,11,14

A a=5&d=3
T20 = 5 + (20 – 1)3 = 62

Sum of an AP:
n
Equation: Sn  a  l 
2
Sn = Sum of ‘n’ terms
n = Number of terms
a = First term
l = Last term

Proof:
Sn = a + (a + d) + (a + 2.d) + (a + 3.d) + … + l …(1)
Sn = l + (l – d) + (l – 2.d) + (l – 3.d) + … + a …(2)
(1) + (2):
2.Sn = n(a + l)
n
 S n  a  l 
2

Luke Cole Page 2


GITIMH3 94107 Sequences & Series Page 3

n
Equation: Sn  2.a  n  1d 
2
Sn = Sum of ‘n’ terms
n = Number of terms
a = First term
d = Common difference

Proof:
From Tn = a + (n – 1)d, Tn = l:
l = a + (n – 1)d …(1)
n
S n  a  l  …(2)
2
Sub (1) into (2):
n
 S n  2.a  n  1d 
2

E.g. Find the sum of all the positive integers less then 100 which are not divisible by 6

A S99 = Sum of positive integer < 100


Sl = Sum of positive integer < 100 which are divisible by 6
ST = S99 – Sl = Sum of positive integers < 100 which are not divisible by 6

99
So, S 99  1  99 
2
S99 = 4950
And, l = 96
n of positive integer < 100 which are divisible by 6 = 96/6 = 16
16
Then, S l  S16  6  96 
2
S16 = 816
 ST = S99 – S16
ST = 4134

Arithmetic Mean:
ac
Equation: x
2
x = Mean
a = First term
c = Last term

Proof:
If a, x & c are an AP then: ac
x–a=c–x  x
2
2.x = a + c

Luke Cole Page 3


GITIMH3 94107 Sequences & Series Page 4

Geometric Sequences or Geometric Progression


(GP)
21/98/98
 A sequence in which each term after the first is formed by multiplying a constant
number, this constant number is referred to as the common ratio ‘r’.

6 18 54
E.g. 2, 6, 18, 54,… Common ratio  r = 3 Since, = =
2 6 18
16 8 4
32, 16, 8, 4,… Common ratio  r = ½ Since, = =
32 16 8

The nth Term of an GP:


Equation: Tn = a.rn – 1
Tn = nth term
a = First term
r = Common ratio
n = Number of terms

Proof:
So, T1 = a
T2 = a.r
T3 = a.r2
 Tn = a.rn – 1

E.g. If T3 = 8 & T6 = – 1, find a, r

A T3 = 8 = a.r2 …(1)
T6 = – 1 = a.r5 …(2)
8
(1)  a  2 …(3)
r
Sub (3) into (2)
8.r 5
1 2
r
 r=–½
Sub r = – ½ into (1)
 a = 32

Luke Cole Page 4


GITIMH3 94107 Sequences & Series Page 5

Sum of an GP:

Equation: Sn 

a 1rn 
r1
Sn = Sum of ‘n’ terms
n = Number of terms
a = First term
r = Common ratio

Proof:
Sn = a + a.r1 + a.r2 + a.r3 + … + a.rn – 1 …(1)
r.Sn = a.r + a.r2 + a.r3 + a.r4 + … + a.rn …(2)
Now (1) – (2):
Sn – r.Sn = a – a.rn

 Sn 

a 1 rn  …[1]
r 1

Geometric Mean:
Equation: x  a .c
x = Mean
a = First term
c = Last term

Proof:
If a, x, & c are an GP then:
x c

a x
x2 = a.c
 x  a .c

Sum to Infinity (Limiting the Sum):


a
Equation: S 
1 r
S = Limited sum to infinity
a = First term
r = Common ratio (– 1 < r < 1)

Proof:
From [1] and for r < 1 & rn  0
a 1  0 
S 
r 1
 S = a/(1 – r)

Luke Cole Page 5


GITIMH3 94107 Sequences & Series Page 6

Consumer Arithmetic
28/10/98
Compound Interest:
Equation: A = P(1 + r)n & I=A–P
A = Amount after ‘n’ time periods
I = Interest
P = Principal
r = Interest rate for ‘n’ time period (%)
n = Number of time periods

E.g. Find the amount that will be in the an after 6 years if $2000 is invested at
12% p.a. with interest paid.
(a) Yearly
(b) ¼ Yearly
(c) Monthly

A (a) r = 12 & n = 6
A = P(1 + r)n
AYearly = 2000(1 + 0.12)6
 AYearly = $3947.65

(b) r = 3 & n = 24
A = P(1 + r)n
A¼ Yearly = 2000(1 + 0.03)24
 A¼ Yearly = $4065.59

(c) r = 1 & n = 72
A = P(1 + r)n
AMonthly = 2000(1 + 0.01)72
 AMonthly = $4094.20

Superannuation:
E.g. A sum of $1500 is invested at the beginning of each year in a super fund. At the
end of 25 years, how much money will be available if the interest rate is 11% p.a.
and it is compounded yearly?

A Year 1: A = 1500(1 + 0.11)25


Year 2: A = 1500(1 + 0.11)24

Year 25: A = 1500(1 + 0.11)1
 Total = Year 1 + Year 2 + …+ Year 25
= 1500(1.111 + 1.112 + …+ 1.1125)
= 1500  GP
= $190 486.16

Luke Cole Page 6


GITIMH3 94107 Sequences & Series Page 7

Time Payments:
 When burrowing money from the bank you owe the bank interest on the balance.

E.g. A sum of $20 000 is borrowed at 12% p.a. interest. If the money is paid back at
regular monthly installments over 4 years, find the amount of each installment?

A 1st Month Amount = (Principal + Interest for the Month) – Installment


2nd Month Amount = (Amount 1) – Installment
4th Year = 12  4 = 48th Month Amount

1st Month: A1 = 20000(1.01) – M


2nd Month: A2 = [20000(1.01) – M](1.01) – M
3rd Month: A3 = 20000(1.01)2 – M(1 + 1.01)

4th Year: A48 = 20000(1.01)48 – M(1 + 1.01 + … + 1.0147)
0 = 20000(1.01)48 – M(1 + 1.01 + … + 1.0147)
200001.01
48
M 
GP
 M = $526.68

Luke Cole Page 7


GITIMH3 94107 Sequences & Series Page 8

Induction
3/11/98
Steps when Proving:
Step 1: Show that the formula is true for the smallest value of ‘n’ (Usually n = 1)
Step 2: Assume that the formula is true for same integer say n = k
Step 3: Prove that the formula is true for n = k + 1
Step 4: State that it is true for n  1 i.e. General Statement

E.g. Prove: 1 + 3 + 5 + … + (2.n – 1) = n2 for n  1

A Prove for n = 1
2(1) – 1 = 12
1=1
Assume true for n = k
1 + 3 + 5 + … + (2.k – 1) = k2
Prove true for ‘n’ = k + 1
1 + 3 + 5 + … + (2.k – 1) + [2(k + 1) – 1] = (k + 1)2
LHS = k2 + [2(k + 1) – 1)
= (k + 1)2
= RHS
If the formula is true for n = k and proven to be true for n = k + 1,
i.e. n = 1, n = 2, n = 3 and so on.
 It is true for any positive integer n  1

Luke Cole Page 8